Clinical and epidemiological evolution of modern therapy and measles in children - V. N. Timchenko; E. B. Pavlova; O. V. Bulina; A. N. Nazarova; O. A. Leonicheva; E. V. Timofeeva (Журнал инфектологии)
Clinical and epidemiological research on the evolution of measles in children in Leningrad – St. Petersburg from 1927–2014 with an analysis of the effectiveness of treatment of this infection. Divided into three periods of fighting «child plague». First period – to use in the practice of specific therapies and antibacterial drugs, characterized by high morbidity, severe weight, high rates of mortality. In the second period the use of donor serum syvotrotki convalescents and sulfa drugs significantly lowered the mortality rate due to the effective treatment of pneumococcal pneumonia. The use of penicillin and broad-spectrum antibiotics led to a further reduction in the severity of measles, a sharp decline in mortality – to tenths and hundredths of a percent. The third period is due to the mass of active immunization against measles, characterized by a significant decline in incidence rates up to her absence in some years. Combined therapy of children with measles in modern conditions with the inclusion etiotropic drugs (Viferon) causes rapid regression of the symptoms of measles, warns layering respiratory viral infection contributes to the smooth course of the disease.